ORGANIZING AND CONDUCTING EXPERIMENTAL WORK ON THE FORMATION OF AN INFORMATION CULTURE FOR FUTURE ENGLISH LANGUAGE TEACHERS - Шуйншкали, Анаргул (Вестник ЗКУ, 2024)
The article considers informational culture formation of future English Language teachers by means of ICT technologies. The task of education today is to create a space for the informational culture formation of an individual that fosters the formation of independent thinking, the perception of the new, the ability to track changes and respond to them and the ability to make decisions in complex and unusual situations, which is possible only if the person is fully informed. Informational culture is a system-forming factor of professional culture of the teacher, as it turns it into an open, self-sufficient, self-developing and self-regulating system. The article proposes the definition of the concept of “informational culture of future English language teacher”. The criteria, indicators and levels of informational culture are justified taking into account the organizational pedagogical conditions that are necessary for it. The proposed set of crite-ria for the effectiveness of the relevant process is based on an understanding of the criterion as a key fea-ture of the process and an understanding of effectiveness as completeness in achieving the planned results. Two indicators correspond to each criterion. The course of the diagnostic-ascertaining stage of the research is described in the context of the selected criteria. The initial levels of informational culture of future Eng-lish language teachers are presented in terms of evaluation criteria and generalized quantitative results of the ascertaining experiment.